Amplification Characteristics of a Coumarin 460-Based Tunable Amplifier - Jianping Shen; Wei Wang; Siwei Zhang (IEEE Photonics Journal, 2020)
We studied the optical signal amplification properties of coumarin 460 (C460) in solution. An optical signal amplification experiment was performed using a side-pumping setup. Amplification of more than 7 dB was achieved over a 13-nm spectral width in the signal wavelength range of 448–461 nm with gains above 10 dB at 448 nm and in the 455–461-nm range. The signal-to-noise ratio (SNR) of the entire band was 5.8–11.1 dB. When the solution concentration and pump energy were 0.001 M (mol/L) and 117 μJ, respectively, the optical gain reached a maximum of 12.25 dB. Thus, the gain and SNR were measured by adjusting the pump energy and solution concentration to determine the optimal concentration of coumarin 460 in methanol solution in the amplifier. Additionally, amplification of the spontaneous emission was found to seriously reduce the SNR, adversely affecting the optical gain.